23. EVALUATION OF PEDICLED SKIN FLAPS WITH SAME AND DIFFERENT FINGER IN COVERING FINGER SKIN LOSS (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluate the coverage ability of the skin flap for each type of finger skin loss wound, the function of the finger after being covered and find out the advantages and disadvantages of the skin flap. Subjects and methods: From January 2019 to January 2024, prospectively examined 55 fingers of 50 patients with finger skin loss wounds treated at the Department of Trauma and Orthopedics, Thong Nhat Hospital. Results: The majority are male, aged 16 - 35, often due to work accidents. Patients with injuries commonly found in fingers I, II, III, combined with areas 2 and 3, mainly receive emergency surgery. The number of cases with a lesion area of less than 2 cm2 accounts for a significant proportion. There were 8 cases of skin flaps with partial purple dermal layer. 100% survival results, no cases of infection. Conclusion: The reverse skin flap with nerve vascular pedicle of the same digit has many advantages in covering skin loss in the bony finger bud area, the flying kite skin flap covers the skin loss area of the I finger, between the I and II fingers and the Moberg skin flap covers well for loss of horizontally beveled or dorsally beveled finger skin. Skin flaps have a high chance of success, good touch feeling, heal quickly and help patients return to life quickly.
Keywords: Pedicled skin flap, finger skin loss.